Antitrust and upstream platform power plays - a policy in bed with procrustes - von Moltke, A (2020)
Ubiquitous digital platforms are fundamentally altering our ways of life. Competition policy-makers, though, are on edge. Among the many issues they are considering, one matter has remained under-appreciated: “upstream” effects. Powerful platforms, consensus has it, are now (or inevitably will be) marshalling our digital markets. They have apparently also found new ways to decimate competition and harm our wallets, menu options, privacy and autonomy. But while antirust academics are furiously debating how best to address such consumer concerns, policy-makers are also reacting to worries expressed by another group of stakeholders, namely (allegedly) victimized suppliers – app developers, merchants, drivers, couriers (etc.), as well as dependent content providers (like Spotify or Yelp), without whom the powerful platforms would have little to attract consumers.